2011
DOI: 10.1029/2011gc003636
|View full text |Cite
|
Sign up to set email alerts
|

The impact of host-rock composition on devolatilization of sedimentary rocks during contact metamorphism around mafic sheet intrusions

Abstract: [1] Sedimentary rocks represent vast reservoirs for hydrous and carbonaceous fluids (liquid or gas) that can be generated and released during contact metamorphism following the emplacement of igneous sill intrusions. A massive release of these fluids may impose perturbations in the global climate. In this study we assess the influence of varying host-rock compositions on the magnitude and type of fluids generated from thermal devolatilization, with particular emphasis on carbon and halogens released from heate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 48 publications
(96 reference statements)
2
52
0
1
Order By: Relevance
“…Many of the relict crystals are quartz grains, as well as occasional phyllosilicates, gypsum, jasper, barite or halite Rodriguez-Losada et al 2015), consistent with H 2 O, CO 2 , CH 4 and SO 2 liberation from hydrous phases, evaporate minerals, calcareous and organic components, and with carbon oxides and H 2 O from degassing quartz grains (cf. Vasiloi et al 1985;Kendrick et al 2006;Aarnes et al 2011). Moreover, the vesicle concentration textures we recorded around relict sedimentary fragments and crystals are virtually identical to textures that have been derived from experiments where quartz was heated to magmatic temperatures.…”
Section: Xeno-pumice Vesicle Size Distributions (Vsds)supporting
confidence: 58%
“…Many of the relict crystals are quartz grains, as well as occasional phyllosilicates, gypsum, jasper, barite or halite Rodriguez-Losada et al 2015), consistent with H 2 O, CO 2 , CH 4 and SO 2 liberation from hydrous phases, evaporate minerals, calcareous and organic components, and with carbon oxides and H 2 O from degassing quartz grains (cf. Vasiloi et al 1985;Kendrick et al 2006;Aarnes et al 2011). Moreover, the vesicle concentration textures we recorded around relict sedimentary fragments and crystals are virtually identical to textures that have been derived from experiments where quartz was heated to magmatic temperatures.…”
Section: Xeno-pumice Vesicle Size Distributions (Vsds)supporting
confidence: 58%
“…Grasby et al (2011) suggested that deposition of coal fl y-ash generated by magma-coal pyrometamorphism in the Siberian province resulted in toxic marine conditions. Black et al (2013) presented modeling to suggest that the halocarbon release from crustal reservoirs associated with Siberian Traps volcanism (Aarnes et al, 2011) could have had signifi cant effects on stratospheric ozone levels. It should be noted that the tropospheric lifetime of halocarbons such as CH 3 Cl is suffi ciently long (>1 yr) that even those released in the lower troposphere reach the stratosphere, reducing the sensitivity of their environmental effects to atmospheric injection.…”
Section: Gas Release From Continental Flood Basalt Eruptionsmentioning
confidence: 99%
“…For example, Ganino and Arndt (2009) have correlated the degree of environmental stress caused by continental fl ood basalt volcanism with the types of sediments beneath the lavas and estimated that emission of CO 2 from contact aureoles with the sedimentary country rock could have been 4-9 times larger than that released from the magma for the Emeishan Traps. In the case of the Siberian Traps, it has been suggested that magma-sediment interactions could dissociate vast quantities of hydrocarbons and halocarbons such as methane from heating of organic-rich shale and petroleum-bearing evaporates (basin-scale gas production potential estimates suggest that metamorphism of organic matter and petroleum could have generated >100,000 Gt CO 2 ), resulting in global warming and ozone depletion (Aarnes et al, 2011;Svensen et al, 2009). The suggested mechanism of gas release is through hydrothermal vent complexes, which are now being recognized as a characteristic component of large igneous provinces (for a review, see Svensen and Jamtveit, 2010).…”
Section: Gas Release From Continental Flood Basalt Eruptionsmentioning
confidence: 99%
“…The heat input associated with the emplacement of large volumes of magma into sill complexes can lead to metamorphic reactions around the sills and to conductive and convective heat transfer (e.g., Aarnes et al, 2015). In the case of the high-TOC Jurassic Lealt shales (Vincent and Tyson, 1999) equivalent to those present at Neist Point, the emplacement of large dolerite intrusions may have caused the production of large volumes of methane (CH 4 ) and potentially subordinate volumes of CO 2 and H 2 O from less dominant calcareous lithologies (Aarnes et al, 2011;Svensen et al, 2015). If the volume of generated fluids was large and the host-rock permeability was low (e.g., shale) and/or capped (e.g., by a lava pile with very low vertical permeability), significant overpressure would have built up in association with the metamorphic aureole of the larger intrusions (Aarnes et al, 2011;Iyer et al, 2013).…”
Section: Hydrothermal Vent Formation Processmentioning
confidence: 99%